2008
DOI: 10.1007/s10393-008-0187-8
|View full text |Cite
|
Sign up to set email alerts
|

Lobomycosis in Bottlenose Dolphins (Tursiops truncatus) from the Indian River Lagoon, Florida: Estimation of Prevalence, Temporal Trends, and Spatial Distribution

Abstract: Lobomycosis (lacaziosis) is a chronic fungal disease of the skin that affects only dolphins and humans. Previous studies have shown a high prevalence of lobomycosis in bottlenose dolphins (Tursiops truncatus) from the Indian River Lagoon, Florida (IRL). We studied the occurrence and distribution of lobomycosis in the IRL using photo-identification survey data collected between 1996 and 2006. Our objectives were to (1) determine the sensitivity and specificity of photo-identification for diagnosis of lobomycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 22 publications
(23 reference statements)
5
92
0
Order By: Relevance
“…The animal had a large region of raised epidermal gray to white nodules over the entire dorsal surface cranial to the dorsal fi n. These lesions are consistent with those seen in the other bottlenose dolphins in this report and lesions seen on bottlenose dolphins from the Indian and Banana rivers in Florida (10). The location of this sighting suggests that this dolphin is of the offshore ecotype (11,12).…”
Section: Live Sightingsupporting
confidence: 84%
See 1 more Smart Citation
“…The animal had a large region of raised epidermal gray to white nodules over the entire dorsal surface cranial to the dorsal fi n. These lesions are consistent with those seen in the other bottlenose dolphins in this report and lesions seen on bottlenose dolphins from the Indian and Banana rivers in Florida (10). The location of this sighting suggests that this dolphin is of the offshore ecotype (11,12).…”
Section: Live Sightingsupporting
confidence: 84%
“…The Indian River Lagoon dolphin population has been assessed for temporal and spatial prevalence of lobomycosis (10). A prevalence of 6.8% was observed in that population from 1996 through 2006, and most cases were observed in the southern portion of this elongate body of water (10).…”
Section: Discussionmentioning
confidence: 99%
“…1) compared with 30% of the animals in the southern portion exhibiting the disease. Based on photographic analysis, another study estimated disease prevalence at 6.8% throughout the lagoon and 4.9% in our study area, the northern part of the IRL (Murdoch et al, 2008). Based on histologic examination, our study documented lacaziosis prevalence to be nearly twice the photographic estimate for the northern portion of the lagoon (3/33 or 9%).…”
mentioning
confidence: 49%
“…The yeast-like, dimorphic fungus, Lacazia loboi (formerly known as Laboa loboi) causes invasive cutaneous lesions in dolphins and humans [58], known as lobomycosis, lacaziosis or keloidal blastomycosis [41,59,62]. The first case of keloidal blastomycosis was described in 1931 in a human patient from the Amazon valley [63].…”
Section: Lacazia Loboimentioning
confidence: 99%
“…On cellular level, the disease presents with superficial granulomatous dermatitis, associated with macrophages and multinucleated giant cells containing a variety of round yeast cells [61]. More cases of this disease affecting cetaceans have been added to the list and recently some authors suggested that the incidence of lobomycosis might represent opportunistic infections in immuno-compromised hosts [62,65]. The bio-accumulation of environmental contaminants in the affected dolphins was thought to possibly contribute to susceptibility to this disease [62].…”
Section: Lacazia Loboimentioning
confidence: 99%